Hukum Takziah dan Permasalahannya - Halimang Halimang (Al-'Adl, 2009)
In this article, studying concerning the meaning of Takziah, in aspect punish and problems of him, All Fuqaha mutually agree to that takziah is sunnah for everybody, good of woman and man, adult and moppet. The legal fundament of for example is Prophet hadis of Muhammad saw which isn’t it by Imam of IbnuMajah and Imam of al-Baihak :“ There no a Mukmin even also which was takziah to you of getting an accident, except Allah swt will put on dignity clothes him at doomsday”. Meaning of takziah according to language comes from the word ‘azza-yu’azzi-ta’ziah mean amusing and having patience with. Having patience with people who remained bypass away their family narrated things able to amuse and lighten the sorrow of them.